Implementasi Pelatihan dan Pengembangan Terhadap Kinerja Karyawan di Bank Syariah Indonesia (BSI) KCP Bima Kartini Kota Bima - Fina Julfiana; Ihwan p. Syamsudin; Ibrahim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The implementation of training at BSI KCP Bima Kartini is still unstructured and has no systematic evaluation. Some employees who have attended the training stated that the material provided is still general and less focused on specific aspects of Islamic banking, such as muamalah contracts, sharia risk management, and sharia product operations. So this study aims to determine the Implementation of Training and Development on Employee Performance at Bank Syariah Indonesia KCP Bima Kartini, Bima City. This research will be conducted at Bank Syariah Indonesia KCP Bima Kartini, Bima City, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques namely Observation, Interview and Documentation. Data Analysis Techniques namely Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study it can be concluded that the implementation of training and development has a very significant role in improving employee performance at Bank Syariah Indonesia KCP Bima Kartini. Training provided regularly, both through face-to-face and online methods, is able to improve technical competence, understanding of sharia products, and quality of service to customers. Employees feel more prepared and confident in carrying out their duties after getting provisions that are in accordance with their work needs.